Metal Graphitic Nanocapsules for Theranostics in Harsh Conditions - Yang, Yanxia; Li, Shengkai; Bu, Hongxiu; Xia, Xin; Chen, Long; Xu, Yiting; Chen, Zhuo (Frontiers in Chemistry, 2022)
Metal nanoparticles (NPs) with superior physicochemical properties and biocompatibility have shown great potential in theranostics. However, metal NPs show poor stability in some harsh conditions such as strong acid, oxidation, corrosion and high-temperature conditions, which limits their extensive bioapplications. To address such issue, a variety of superstable metal graphitic nanocapsules with the metal cores confined in the nanospace of few-layer graphitic shell have been developed for biodetection and therapy in harsh conditions. In this mini-review, we summarize the recent advances in metal graphitic nanocapsules for bioapplications in harsh conditions. Firstly, their theranostic performance in non-intrinsic physiological harsh environment, including oxidation, corrosion and high-temperature conditions, is systematically discussed. Then, we highlight their theranostic performance in the harsh stomach condition that is strong acidic and pepsin-rich. It is expected that this review will offer inspiration to facilitate the exploitation of novel theranostic agents that are stable in harsh conditions.